Identity of the subalpine-subarctic corticioid fungus Megalocystidium leucoxanthum (Russulales, Basidiomycota) and six related species - Spirin, Viacheslav; Volobuev, Sergey; Malysheva, Vera; Miettinen, Otto; Kotiranta, Heikki; Larsson, Karl-Henrik (Plant Ecology and Evolution, 2021)
Background and aims - To date, Megalocystidium leucoxanthum, a corticioid fungus originally described from the Italian Alps, was considered as a widely distributed species inhabiting numerous angiosperm hosts in the northern hemisphere. Its specimens collected in different geographic areas and from various host species revealed a high morphological variability and thus obfuscated differences from the closely related M. luridum. The objective of this study was to re-establish M. leucoxanthum based on newly collected and sequenced specimens and clarify the identity of morphologically deviating collections previously ascribed to this species. Material and methods - In total, 87 specimens of Megalocystidium spp. (including two historical types) were studied by morphological methods. Their phylogenetic relations were investigated based on DNA sequences (nrITS, nrLSU, and tef1) of 29 specimens. Key results - Based on morphological, ecological and DNA data, we showed M. leucoxanthum sensu typi is a rare species restricted to Alnus alnobetula in subalpine and subarctic zones. Consequently, records from other hosts (mostly representatives of Salicaceae) belong to three other species, M. olens, M. perticatum, and M. salicis, described as new to science. The fourth newly introduced species, M. pellitum, occurs on the same host tree as M. leucoxanthum but it can be separated from the latter due to distinctive morphological traits and DNA sequences. Additionally, Aleurodiscus diffissus is combined in Megalocystidium and the identity of M. luridum is clarified. Peer reviewed